ХОТИНСЬКА БИТВА 1621 РОКУ. ІГНОРОВАНЕ ДЖЕРЕЛО В УКРАЇНСЬКІЙ ІСТОРІОГРАФІЇ/ KHOTYN BATTLE 1621. IGNORED SOURCE IN UKRAINIAN HISTORIOGRAPHY - Antoniy MOYSEY; Arkadiy MOІSEY (Актуальні питання суспільних наук та історії медицини, 2021)
The article offers a historiographical consideration of the description of the Khotyn battle 1621with an emphasis on the historical value of M. Kostin's “Chronicle of the Land of Moldova” in the coverage of the event. The relevance of the study is dictated by the 400th anniversary of the battle. The purpose of the study is to clarify the historical significance of the chronicle in revealing the theme of the Battle of Khotyn in 1621. Methodology describes the work of M. Kostin, its source base, comparison with other historical sources, review of its use. Conclusions. “Chronicle of the Land of Moldova” by Myron Kostin, being the only source for studying the history of Moldova in the early and mid seventeenth century. at the same time it is a true description of the events of the Khotyn War (1620–1621). Although the chronicler is not a contemporary of the events, his account of the Battle of Khotyn is based on serious Polish sources of the relevant era, oral information from contemporaries of the fighting, the traditions of the princely family of Movileshty, and so on. The work is positively characterized by a deep and detailed description of events, impartiality, clear analysis of military operations of a participant in many battles, education of the author and his broad outlook, which allowed him to understand the causal links of actions, actions of the parties, unconditional literary talent M. Kostin. His disregard for the events of the Khotyn War of 1621 by a number of Ukrainian historians shows a reluctance to consider the event comprehensively, using all sources. Moreover, we see a focus on showing only one fragment of this historical event, the participation of the Ukrainian side in it. The language barrier to the use of the Chronicle is no more a problem than a political motive.